ChatGPT for sustainability reporting research: A bibliometric analysis of scholarly output - Fauzan; Bakri, Mohammed Hariri; Jumbri, Isma Addi; Setiyowati, Supami Wahyu; Sulistyo; Mustikowati, Rita Indah; Subagiyo, Rokhmat (SHPMedia Sdn Bhd, 2024)
Sustainability reporting refers to the study of disclosing information about an organisation's social, environmental and economic performance to meet stakeholder expectations regarding sustainability. This article aims to discover (1) how research on sustainability reporting grows yearly. (2) What are the trends and gaps in the study of sustainability reporting? and (3) Who are the most influential writers in the study of sustainability reporting, and how do they collaborate? ChatGPT was used to answer the objectives of this research. The ChatGPT AI chatbot can significantly assist in assessing and reviewing research on sustainability reporting. The method used is a combination of Chatbot AI ChatGPT and bibliometric analysis. While data analysis uses VOSviewer, Publish or Perish, and biblioMagika® software. The results of the study show that there is a significant increase in studies regarding sustainability reporting. Researchers collaborate through various academic activities, such as joint research, writing joint articles, and conferences. In principle, these results should be applicable across research domains. From these findings, the theoretical implication is adding to the sustainability reporting literature, with a bibliometric analysis approach using chatGPT. There are advantages to idea generation and data identification. However, technologically the synthesis of literature is still weak. The researcher's expertise in communicating with AI ChatGPT is a key factor in determining the quality of the output. This new technology needs to consider its implications, especially its ethical implications.